2016
DOI: 10.1016/j.imbio.2016.06.165
|View full text |Cite
|
Sign up to set email alerts
|

Complementary roles of the classical and lectin complement pathways in the defense against Aspergillus fumigatus

Abstract: Aspergillus fumigatus infections are associated with a high mortality rate for immunocompromised patients. The complement system is considered to be important in protection against this fungus, yet the course of activation is unclear. The aim of this study was to unravel the role of the classical, lectin, and alternative pathways under both immunocompetent and immunocompromised conditions to provide a relevant dual-perspective on the response against A. fumigatus. Conidia (spores) from a clinical isolate of A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…We measured the binding of various recombinant and serum-purified MASPs to heat-inactivated A. fumigatus conidia strain 6871 by flow cytometry. We have previously seen that heat inactivation does not compromise the binding of complement components [13]. The results showed that both rMASP-1 and rMASP-3, and to a minor degree rMASP-1/-3 heavy chain, bound to A. fumigatus .…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…We measured the binding of various recombinant and serum-purified MASPs to heat-inactivated A. fumigatus conidia strain 6871 by flow cytometry. We have previously seen that heat inactivation does not compromise the binding of complement components [13]. The results showed that both rMASP-1 and rMASP-3, and to a minor degree rMASP-1/-3 heavy chain, bound to A. fumigatus .…”
Section: Resultsmentioning
confidence: 80%
“…To further investigate the consequence of MASPs binding to the surface of A. fumigatus , we tested the effects in human serum. More specifically, in MBL-defect serum combined with a C1q inhibitory mAb to exclude the contribution from previously identified classical and lectin pathway activation on A. fumigatus [13]. Figure 8a and b shows a tendency that prebound rMASP-1 and MASP-3 increased the C4b deposition and that rMASP-1 was able to induce a higher C3b deposition than rMASP-3.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations